Spore dispersal, diurnal pattern and viability of Monilinia spp. conidia and the relationship with weather components in an organic apple orchard - Abonyi, F.; Vámos, A.; Rózsa, A.; Lakatos, P.; Holb, I. J. (International Journal of Horticultural Science, 2015)
In a two-year Hungarian study, spore dispersal diurnal periodicity and viability of Monilinia spp. and their relation to weather components were determined in an organic apple orchard. Conidia of Monilinia spp. were first trapped in late May in both years. Low number of conidia were trapped until end-June. Thereafter, number of conidia continuously increased until harvest. Conidia in a 24-h period showed diurnal periodicity pattern, with th highest concentration in the afternoon hours. Spore viability with FDA staining showed that viability of conidia ranged from 45 to 70% with showing lower viability in the dry than in the wet days in both years. Temperature and relative humidity correlated positively with mean hourly conidia numbers in both years. Mean hourly rainfall was negatively but poorly correlated with conidiacatches in both years. Results were compared and discussed with previous observations.